Traditional Spiritual Values as a Glocal Basis for the Interpretation of Axiological Concepts in Film Discourse - Aishat M. Aibazova (Актуальные проблемы филологии и педагогической лингвистики, 2024)
The article studies multimodal verbal, visual and auditory mechanisms of contamination of universal, global and national value spaces in the aspect of dominant axiological concepts’ interpretation of regional film discourse. Film discourse can be considered as the most representative field for the shift of value dominants, combining various semiotic code systems for the most effective implementation of the perlocutionary effect, pursuing the main goal of transforming the conceptual and value space of the recipient. As part of the analysis of the key methods of glocalization of axiologems, a complex of methods of the hermeneutic and interpretative approach was used, including contextual, linguacultural, etymological, linguaaxiological, discursive and modal methods. The polymodal and polycode nature of the empirical material requires systematic consideration of ways to intensify traditional spiritual values in their verbalization. The key method of contaminating tradition and innovation in modifying the content of axiological concepts is a constitutive link to global, universal components shared by other ethnonational communities. Such an association occurs in the context of the expansion of the positive and negative spaces of the described concept deportation, which is significant both for the Karachay-Balkarian linguaculture under consideration and for many peoples of the USSR. The concept represents a whole precedent world, including individual concepts for concretizing values and anti-values in a situational and local rethinking. The key axiological concepts in the translation of traditional values and anti-values of the deportation are recognized as jashau (“life”), as a global axiologeme, with the concept of elum/ajal (“death”) leveled out and thrown to the periphery; as well as private locally interpreted concepts bilim (“knowledge”), syy/namys (“dignity/honor”), kishilik (“courage”), azatlyk (“freedom”). The overtones of universal perception in the generalized content of these concepts make it possible to create a glocalized space of interpretation that reflects common values and meanings in the ethno-national linguistic consciousness.